2019
DOI: 10.1111/jgs.15773
|View full text |Cite
|
Sign up to set email alerts
|

Review of Programs to Combat Elder Mistreatment: Focus on Hospitals and Level of Resources Needed

Abstract: Background Elder mistreatment is common and has serious social and medical consequences for victims. Though programs to combat this mistreatment have been developed and implemented for more than three decades, previous systematic literature reviews have found few successful ones. Objective To conduct a more comprehensive examination of programs to improve elder mistreatment identification, intervention, or prevention, including those that had not undergone evaluation. Design Systematic review. Setting Ovid MED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 60 publications
(106 reference statements)
0
36
0
1
Order By: Relevance
“…We also focused on passion at team level because the team is a central component of health care. Patient care depends on the quality of teamwork, since communication and coordination in health care units are crucial mechanisms to address complex therapies (Rosen et al, 2019). We argue that passion at team level provides energy-building engagement in valued activities.…”
Section: Introductionmentioning
confidence: 92%
“…We also focused on passion at team level because the team is a central component of health care. Patient care depends on the quality of teamwork, since communication and coordination in health care units are crucial mechanisms to address complex therapies (Rosen et al, 2019). We argue that passion at team level provides energy-building engagement in valued activities.…”
Section: Introductionmentioning
confidence: 92%
“…It is critically important that healthcare providers are well trained to address the complex needs of abused older adults and prevent their further victimization ( Rosen et al, 2019 ). This e-learning curriculum showed promise in training forensic nurses across Ontario to appropriately respond to elder abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Those experiencing abuse are also more likely to be hospitalized, visit an emergency department, and use behavioral health services ( Yunus et al, 2019 ). A recent review of various types of responses to elder abuse across the globe indicated that hospitals offer a promising point for intervention ( Rosen et al, 2019 ). However, a recent European study found that the level of knowledge and skills of many healthcare professionals working in hospitals specifically related to detecting and responding to elder abuse is limited, and further education and training has been recommended ( Corbi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the growing number of intervention studies on elder abuse, research synthesis on the pooled effect for elder abuse interventions remains lacking. From the limited available systematic reviews of elder abuse intervention programs, either found a lack of sufficient evidence to establish the effectiveness of elder abuse ( Ploeg et al, 2009 ; Alt et al, 2011 ; Fearing et al, 2017 ) programs or programs that did not use rigorous evaluations to assess the effectiveness of said programs ( Rosen et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%